2023
DOI: 10.1111/cup.14377
|View full text |Cite
|
Sign up to set email alerts
|

A call for nail clipping histopathology to become an essential component of the routine evaluation of melanonychia: Benefitting patients as a triage and surgical planning maneuver

Abstract: We call on dermatologists and dermatopathologists to include nail clipping histopathology as an essential component of the routine evaluation of melanonychia. This manuscript demonstrates a case where an adult woman with broad melanonychia of the right thumbnail declined a nail matrix biopsy, but was amenable to a nail clipping.The nail clipping showed pigmentation, melanocyte remnants, and small cavities in the nail plate. These features have been published previously by our group as a clue to nail unit melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…For LM cases, a nail matrix biopsy is the ideal way to distinguish between benign and malignant causes of melanonychia. However, nail clipping can be a useful, non-invasive tool to aid in surgical planning, as it can help localize pigment within the nail plate and can be used as a rapid triage maneuver to detect cases in which urgent nail matrix biopsy is needed [ 37 ]. A pigment found in the dorsal aspect of the nail plate localizes lesions to the proximal matrix, while pigment in the ventral aspect of the nail plate localizes to the distal matrix [ 38 ].…”
Section: Diagnosismentioning
confidence: 99%
“…For LM cases, a nail matrix biopsy is the ideal way to distinguish between benign and malignant causes of melanonychia. However, nail clipping can be a useful, non-invasive tool to aid in surgical planning, as it can help localize pigment within the nail plate and can be used as a rapid triage maneuver to detect cases in which urgent nail matrix biopsy is needed [ 37 ]. A pigment found in the dorsal aspect of the nail plate localizes lesions to the proximal matrix, while pigment in the ventral aspect of the nail plate localizes to the distal matrix [ 38 ].…”
Section: Diagnosismentioning
confidence: 99%
“…As melanocytes do not typically reach the keratogenous zone in benign proliferations, the presence of melanocytes in the nail plate of an adult is a useful clue to the diagnosis of melanoma. 24,40,59 One study found that a large number and density of large cellular remnants of melanocytes in the nail plate with more dispersion toward the distal side can be suggestive of an invasive NUM. 60 Of note, in our experience, S100 stain can best identify the melanocytic remnants within the nail plate, while MART1 staining may be negative.…”
Section: Nail Plate Evaluationmentioning
confidence: 99%
“…12 Another diagnosis in which a biopsy of only the nail plate can be very useful is nail melanoma. 13,14 Evidence of melanocytes spreading across the nail plate of an adult in a pagetoid pattern is a highly suggestive sign of melanoma (Fig. 2B).…”
Section: Nail Platementioning
confidence: 99%